ANALYSIS OF THE INFLUENCE OF SUSTAINABLE LEADERSHIP IN FACING VUCA CHALLENGES ON ESG IMPLEMENTATION IN PRIVATE COMPANIES - Fauziah Nur Simamora; Irman Puansah; Rizki Baroroh; Kaharuddin; Abdul Rasid (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
With the acceleration of global disruption and increased governance pressures, companies can no longer rely on short-term profitability; organizational resilience and sustainability are at stake. This study aims to examine the role of sustainable leadership in driving the implementation of Environmental, Social, and Governance (ESG) in private companies in Central Tapanuli Regency, facing the challenges of VUCA (Volatility, Uncertainty, Complexity, and Ambiguity). This study addresses a domain rarely explored in the sustainable leadership literature and is expected to enrich the empirical data. The research approach used a quantitative explanatory approach with a cross-sectional survey design. Respondents were leaders, managers, and supervisors in private companies that had been operating for at least three years and had a formal management structure, recruited through purposive sampling. The test results showed that the corrected item-total correlation value was above the table r value (0.300), while the Cronbach's Alpha value for both variables was above 0.8, indicating excellent reliability. The normality test confirmed that the data were normally distributed (Asymp. Sig. = 0.147 > 0.05). Pearson correlation analysis showed a significant influence between sustainable leadership and ESG implementation (r = 0.521), with a coefficient of determination of 27.1%, which means that variations in ESG implementation can be explained by sustainable leadership by a proportion, while the rest is influenced by other factors outside the model. The simple linear regression equation obtained is Y = 44.215 + 0.394X, and the results of the t-test (t count 3.453 > t table 2.037; significance 0.000 < 0.05) confirm that the influence of sustainable leadership on ESG implementation is positive and statistically significant. This finding implies that strengthening long-term oriented leadership capacity is one of the strategic levers for private companies in natural resource-based regions to realize more substantive ESG practices, not just formal regulatory compliance